2001
DOI: 10.1097/00005537-200101000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation Therapy for Head and Neck Cancer Including Carotid Artery Involvement

Abstract: We found EPT to be safe and efficacious in patients with head and neck cancer, even with internal carotid artery involvement. Patients with early stage recurrences have the potential for prolonged survival beyond 2 years without the morbidity of surgery and radiation or toxicity of systemic chemotherapy. Because of its superb access qualities even for bulky tumors, EPT is a potential method of delivery for other tumoricidal agents such as in genetic-altering schemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
0
53
0
Order By: Relevance
“…The novel therapies, bleomycin electrochemotherapy and IL-12 electrogenetherapy, have shown antitumor effect in a variety of tumors (6,15,16) and in the induction of antitumor immune memory (23, 25 -27). The challenge is that IL-12 electrogenetherapy cannot eradicate either large volume tumors or high-grade malignant tumors (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel therapies, bleomycin electrochemotherapy and IL-12 electrogenetherapy, have shown antitumor effect in a variety of tumors (6,15,16) and in the induction of antitumor immune memory (23, 25 -27). The challenge is that IL-12 electrogenetherapy cannot eradicate either large volume tumors or high-grade malignant tumors (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…administration (12 -14). Clinical trials using bleomycin electrochemotherapy for treating SCC and adenocarcinoma have been conducted in both Europe and the United States (15,16). The clinical trial data showed a complete response in 80% of primary tumors and 26% of recurrent tumors in patients (http://www.genetronics.com).…”
mentioning
confidence: 99%
“…In veterinary medicine several studies have already demonstrated the effectiveness, convenience and safety of ECT with either cisplatin or bleomycin for the treatment of spontaneous tumors, such as soft-tissue sarcomas in cats, mast cell tumors and perianal tumors in dogs and sarcoids in horses [8][9][10][11][12][13][14]. In clinical settings ECT is currently used with palliative intent for the treatment of predominantly melanoma cutaneous metastases, as well as in head and neck tumors, basal cell carcinomas, and adenocarcinomas in humans [15][16][17][18][19][20][21][22][23][24]. ECT has also been used in the treatment of primary basal cell carcinoma with very high success rate [25,26].…”
mentioning
confidence: 99%
“…33,34 Studies have shown that RE in combination with bleomycin therapy is safe and improves outcomes for the treatment of squamous cell carcinoma of the head and neck when compared with bleomycin therapy alone. 35,36 …”
Section: Reversible Electroporationmentioning
confidence: 99%